PERANAN KPPU DALAM MENEGAKKAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - I Ketut Karmi Nurjaya (Jurnal Dinamika Hukum, 2009)
Law No. 5/1999 regardingthe prohibition of monopoly practices and unfair Businesss Competition has been established on 5 March 1999 and was effective on 5 September 2000. Through the establishment of Law No 5/1999 it is hope that fair competition will be created, therefore market economy will rise effectively. The implementation of Law No.5/1999is entrusted to and implemented by Komisi Pengawas Persaingan Usaha/KPPU (Supervisory Commission for Business Competition) that has already been established through Presidential Decree No. 75/1999 about Komisi Pengawas Persaingan Usaha.The role that can be taken by KPPU is taking action in accordance with the out bority of the commission as reffered to in article 36 especially in concluding the result of investigation and/or examination whether there are or are not any monpoly practices and/or unfair busines competition, also deciding and determining whether or not there has been any loss inffered by other business actors or public.  Kata kunci: Peranan KPPU, Praktek Monopoli